Effectiveness of E-Learning Platforms in Higher Education: A Comparative Literature Review (2020–2025) - Abdul Aziz bin AB Nasir; Rosnida Binti Baharuddin; Ramzi Y Wan (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
E-learning has become a vital pillar in higher education, especially since the COVID-19 pandemic forced a sudden shift towards digital learning methods. This article examines the effectiveness of e-learning platforms through a comparative literature review (2020–2025), focusing on Moodle, Google Classroom, Microsoft Teams, Zoom, and CIDOS 4.0 as the local platform. The study evaluates aspects of student engagement, accessibility, assessment, and technological innovation. Findings reveal that although e-learning enhances flexibility, challenges remain in terms of the digital divide, system usability, and reliability of assessment. This review highlights that Moodle provides strong interactive and assessment features, while Google Classroom offers simplicity and accessibility but lacks advanced analytics. Microsoft Teams supports collaboration and integration with Office 365, yet requires stable internet. Zoom is highly effective for synchronous interaction but less suitable for task management. CIDOS 4.0 addresses Malaysia’s TVET context but continues to face issues with server stability and user interface design. Beyond platform-specific strengths and weaknesses, the analysis emphasizes that student engagement, fair access, and reliable evaluation methods are central to e-learning effectiveness. Hybrid approaches that combine face-to-face and online learning are identified as the most effective strategy within the Malaysian higher education context. The study concludes that institutions must not only choose appropriate platforms but also enhance digital literacy, invest in infrastructure, and explore innovations such as AI and gamification. These measures can maximize e-learning’s potential to improve teaching, learning quality, and the broader digital transformation of higher education.